Determining the attractiveness of Serbian spas as a destination for wellness tourism - Belij-Radin Marija (Glasnik Srpskog Geografskog Društva)
Serbia has a long tradition in the development of spa tourism, which is mainly intended for domestic tourists. As a result of current trends in tourism, especially changes in tourist demand, destinations are also changing. For many countries, the development of wellness tourism is an important way to create a competitive advantage. The paper presents the study of attractiveness characteristics of spa resorts in Serbia and then ranks the spa resorts according to these factors. The model used in the research consists of 24 factors (grouped into 6 groups) that influence the attractiveness of spas as spa and wellness tourism destinations. The research included twenty spas and the survey was conducted among experts in the field of tourism. The most important factors influencing the attractiveness of spas as spa and wellness tourism destinations are: The attractiveness of the range of health and wellness treatments offered in spas (0.349), the natural conditions and relaxing atmosphere of spas (0.206) and price competitiveness (0.172).